Romania : Ex-Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews the experience of the IMF's long-term engagement in Romania and options for future IMF involvement. The unfavorable growth performance also reflected adverse conditions for private sector development. Foreign investors have welcomed the more stable macroeconomic environment and the tax legislation overhaul under the recent Stand-By Arrangement. Although the overlap between Bank and IMF conditionality in the area of structural reforms was not conducive to reducing the number of conditions, it helped increase the pressure on the authorities to maintain the reform momentum.